The Correlation of Simple Present Tense and Creative Thinking in Writing Descriptive Text - Arrum Sari (Foremost Journal, 2020)
ABSTRACT The aim of this research is whether there is a correlation of simple present tense mastery, creative thinking and ability in writing descriptive text. The population of this study is eleventh grade students in SMAN 13 Kabupaten Tangerang. The writer used 77 students as a sample of this research which determined by using a sample random sampling. In this research, the researcher used quantitative descriptive method. There are three variables in this research, studentsÂ’ simple present tense mastery as first independent variable, creative thinking as second independent variables, and descriptive writing skill as dependent variable, the technique of collecting data was using tests and questionnaire. The findings of this research reveal that there is a significant correlation of simple present tense mastery, creative thinking and ability in writing descriptive text at SMAN 13 Kabupaten Tangerang 2020/2021. The result can be concluded that Fcount > Ftable which there was a positive significant relation between simple present tense mastery, creative thinking and writing descriptive text at eleventh grade of SMAN 13 Kabupaten Tangerang.   Keywords: Creative Thinking, Descriptive text, Simple Present Tense Mastery, and Writing Skill